A SHPB Experimental Study on Dynamic Mechanical Property of High-Damping Rubber - Xiudi Li; Huaiyuan Mao; Ke Xu; Chaoyang Miao (Shock and Vibration)
A split Hopkinson pressure bar (SHPB) experiment was done to examine the feasibility and explosion resistance of high-damping rubber materials developed for use in the area of antiexplosion applications. Through the experiment, the dynamic mechanical properties of the high-damping rubber were determined. The existence of dynamic compressive stress-strain curves at various strain rates of the high-damping rubber have been confirmed from the SHPB experiment. The variation law of the dynamic compression performance with the strain rate is studied, and the energy absorption characteristics of high-damping rubber materials are analyzed. To study the microstructural changes of the high-damping rubber before and after impact, a scanning electron microscopy (SEM) test was done. The results indicated that the stress-strain curve and dynamic modulus of high-damping rubber has an obvious strain rate effect, and the strength and energy absorption ability of high-damping rubber material increases with an increase in the strain rate; the ideal energy absorption efficiency of high-damping rubber can reach 0.8 at a high strain rate and the ideal energy absorption efficiency is more than 0.5 in a wide deformation range; when compared with aluminum foam, the energy absorption effect for high-damping rubber is more apparent. In the event of a compressed deformation or the creation of holes, there may be a change in the main internal mechanism of the high buffering and energy absorption capacity of the high-damping rubber.